2017
DOI: 10.1186/s12875-017-0643-z
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing the right thing’: factors influencing GP prescribing of antidepressants and prescribed doses

Abstract: BackgroundAntidepressant prescribing continues to increase, with 5-16% of adults receiving antidepressants annually. Total prescribing growth is due in part to increased long-term use, greater selective serotonin re-uptake inhibitor (SSRI) use and the use of higher SSRI doses. Evidence does not support routine use of higher SSRI doses for depression treatment, and factors influencing the use of such doses are not well known. The aim of this study was to explore factors influencing GPs’ use of antidepressants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 45 publications
6
42
0
Order By: Relevance
“…Firstly, many GPs in this study reported understanding patients’ emotional concerns as due to life stress. This is reflected in the literature, where GPs report tensions between being trained to approach emotional concerns as a biomedical issue, and their own beliefs that emotional concerns result from life stressors (Dew et al, ; Johnson et al, ; Thomas‐MacLean et al, ). As a result, some GPs preferred to utilise a multifaceted treatment approach including social prescribing (Johnson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, many GPs in this study reported understanding patients’ emotional concerns as due to life stress. This is reflected in the literature, where GPs report tensions between being trained to approach emotional concerns as a biomedical issue, and their own beliefs that emotional concerns result from life stressors (Dew et al, ; Johnson et al, ; Thomas‐MacLean et al, ). As a result, some GPs preferred to utilise a multifaceted treatment approach including social prescribing (Johnson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…GPs report tensions between being trained to approach emotional concerns as a biomedical issue, and their own beliefs that emotional concerns result from life stressors (Dew et al, 2005;Johnson et al, 2017;Thomas-MacLean et al, 2005). As a result, some GPs preferred to utilise a multifaceted treatment approach including social prescribing (Johnson et al, 2017).…”
Section: What Work Well Strategies Quotesmentioning
confidence: 99%
“…Of the three full papers assessed, two were excluded (no data on attitudes, beliefs, feelings, perceptions on continuing or discontinuing antidepressant use n=1, did not use qualitative data collection and analysis n=1). A total of 22 papers reporting 22 studies were therefore included in our review (Karp, 1993;Knudsen et al, 2002;Pollack and Grime, 2002;Hoogen, 2006;Verbeek-Heida and Mathot, 2006;Holt, 2007;Johnston et al, 2007;Leydon et al, 2007;Wilson, 2007;McMullen and Herman, 2009;Aselton, 2010;Dickinson et al, 2010;McKinney and Greenfield, 2010;Iden et al, 2011;Schofield et al, 2011;Buus et al, 2012;Bayliss and Holttum 2015;Eveleigh, 2015;Nygaard et al, 2015;Weaver, 2015;Bosman et al, 2016;Johnson et al, 2017). Of note, no potentially relevant titles and abstracts were excluded solely on the basis of being non-English language publications.…”
Section: Study Selectionmentioning
confidence: 99%
“…The reasons for potential antidepressant overprescribing in our study remain unclear, but may include the availability of agents that are safer for use in the elderly, the improved detection of emotional distress in geriatric patients, and the increasing use of antidepressants in general practice . The challenges associated with managing a large number of co‐occurring chronic health conditions during brief office visits may also be an important factor–one that we were unable to assess directly in this research. However, potential antidepressant overprescribing in our study was associated with factors representing higher clinical complexity or severity.…”
Section: Discussionmentioning
confidence: 99%